Sustainable development goals law, theory and implementation - edited by Duncan French (Cheltenham Edward Elgar Publishing, 2018)
Building on the previously established Millennium Development Goals, which ran from 2000-2015, the 2015 Sustainable Development Goals (SDGs) provide the UN with a roadmap for development until 2030. This topical book explores the associated legal and normative implications of these SDGs, which in themselves are not legally binding.
Includes index
Keywords: Sustainable development -- Law and legislation